2015
DOI: 10.1111/jan.12830
|View full text |Cite
|
Sign up to set email alerts
|

Screening for infertility‐related stress at the time of initial infertility consultation: psychometric properties of a brief measure

Abstract: The Infertility-Related Stress Scale showed evidence of validity and reliability. This new, brief self-report can assist fertility clinic staff in identifying those patients who need support to overcome the stressful impact of infertility on intrapersonal and interpersonal domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 76 publications
5
24
1
6
Order By: Relevance
“…For the present study, items were summed up to obtain a total score ranging from 12 to 60, with higher scores representing higher levels of infertility‐related stress. In the original validation study conducted on a sample of 597 Italian infertile women and men, the total IRSS had a Cronbach's α reliability coefficient of 0.91, and positively correlated with measures of emotional distress, supporting construct validity (Casu & Gremigni, ). The IRSS was translated from Italian into Portuguese and then back‐translated by two independent bilingual psychologists for the present study, according to standard procedures (van de Vijver & Hambleton, ).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…For the present study, items were summed up to obtain a total score ranging from 12 to 60, with higher scores representing higher levels of infertility‐related stress. In the original validation study conducted on a sample of 597 Italian infertile women and men, the total IRSS had a Cronbach's α reliability coefficient of 0.91, and positively correlated with measures of emotional distress, supporting construct validity (Casu & Gremigni, ). The IRSS was translated from Italian into Portuguese and then back‐translated by two independent bilingual psychologists for the present study, according to standard procedures (van de Vijver & Hambleton, ).…”
Section: Methodsmentioning
confidence: 89%
“…Infertility‐related stress was measured with the Infertility‐Related Stress Scale (IRSS; Casu & Gremigni, ). This 12‐item self‐report measures the impact of infertility in the intrapersonal (e.g., how much stress the infertility problem places on physical well‐being) and interpersonal (e.g., how much stress the fertility problem places on relationships with friends) domains of life.…”
Section: Methodsmentioning
confidence: 99%
“…In past decades, most infertility studies have focused on women. A review of 33 studies revealed that women had more negative experiences with infertility than men in many domains, such as depression, anxiety, stigmatization, self-esteem, stress, and identity (Casu & Gremigni, 2016;Ying, Wu, & Loke, 2016). However, male infertility has historically been an overlooked problem (Ahmadi, Montaser-Kouhsari, Nowroozi, & Bazargan-Hejazi, 2011;Mehta, Nangia, Dupree, & Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies examining the infertility stress have focused on couples, most of the studies were indicative of the higher mean score of infertilityrelated stress in women than that in men (9,11,16,17). Moreover, the women who are seeking treatment are subjected to depression and anxiety more than men (9,18).…”
Section: Introductionmentioning
confidence: 99%